PENGARUH PENERAPAN SISTEM E-FILING, PENGETAHUAN PERPAJAKAN TERHADAP KEPATUHAN WAJIB PAJAK DENGAN SOSIALISASI PERPAJAKAN SEBAGAI VARIABEL MODERATING (Studi Kasus Pada Wajib Pajak Orang Pribadi yang Terdaftar di KPP Pratama Semarang Timur) - Setiyarini, Indri; Mohklas, Mohklas (JAB (Jurnal Akuntansi & Bisnis), 2017)
One of Indonesia's largest sources of income is tax, but the problem is that there is still a minimum or less than the revenue target for each year. The analysis of the cause is that because in the official assessment system the levy responsibility lies entirely with the government, the awareness of the taxpayer is still low, it is still supported by an electronic system, and the socialization of the new system, for example E-Filing is not yet or less significant.This study aims to examine, analyze the effect of the application of the E-Filing system, taxation knowledge of taxpayer compliance with taxation socialization as a moderating variable.The population in this study is an individual taxpayer who is registered in the East Semarang Primary Tax Office. Sampling was carried out using random sampling method and the number of samples was 99 respondents. This study uses a questionnaire in its data collection. The analysis technique used is validity test, reliability test, classic assumption test including normality test, multicollinearity test, heteroscedasticity test. Hypothesis testing in this study using multiple linear regression analysis and MRA test (Moderated Regression Analysis).The results showed that the application of the E-Filing system had a positive and significant effect on taxpayer compliance, with a significance value of 0.001, tax knowledge had no significant negative effect on taxpayer compliance, with a significance value of 0.122, taxation socialization could moderately / negatively strengthen the relationship between E-Filing and taxpayer compliance, with a significance value of 0.015, and tax socialization can moderate / positively strengthen the relationship between tax knowledge and taxpayer compliance, with a significance value of 0.010.Â Keywords: Application of E-Filing System, Taxation Knowledge,Â Taxation and Taxpayer Compliance Socialization.